2010
DOI: 10.4103/0256-4947.62833
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity in Saudi children and adolescents

Abstract: BACKGROUND AND OBJECTIVE:There is limited information on overweight and obesity in Saudi children and adolescents. The objective of this study was to establish the national prevalence of overweight and obesity in Saudi children and adolescents.METHODS:The 2005 Saudi reference data set was used to calculate the body mass index (BMI) for children aged 5 to 18 years. Using the 2007 WHO reference, the prevalence of overweight, obesity and severe obesity were defined as the proportion of children with a BMI standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
157
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(181 citation statements)
references
References 28 publications
11
157
3
1
Order By: Relevance
“…The possible explanations could be that the screen time may displace more active pursuits, advertising of junk food and fast food increases children's requests for those particular foods and products, snacking increases while watching TV or movies, and late-night screen time may interfere with getting adequate amounts of sleep, which is a known risk factor for obesity (Telford et al, 2012). This finding was in agreement with a recent study conducted in Saudi Arabia, which revealed that the prevalence of obesity among the school children was increased with increase in hours of watching TV (El Mouzan et al, 2010). Another Canadian study reported that, the odds of being overweight increased by 8% for every 30 minutes of additional time spent in watching television between school and dinner on a typical school day (Strasburger, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…The possible explanations could be that the screen time may displace more active pursuits, advertising of junk food and fast food increases children's requests for those particular foods and products, snacking increases while watching TV or movies, and late-night screen time may interfere with getting adequate amounts of sleep, which is a known risk factor for obesity (Telford et al, 2012). This finding was in agreement with a recent study conducted in Saudi Arabia, which revealed that the prevalence of obesity among the school children was increased with increase in hours of watching TV (El Mouzan et al, 2010). Another Canadian study reported that, the odds of being overweight increased by 8% for every 30 minutes of additional time spent in watching television between school and dinner on a typical school day (Strasburger, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, our results were much lower than [13] in Kuwait. Concerning the prevalence of obesity, our results were in agreement with [10] [11], but it was higher than [9] [12] and [13]. Apart from Kuwait, all of these studies showed nearly similar rates of overweight, while the prevalence of obesity showed marked variation.…”
Section: Discussionsupporting
confidence: 81%
“…As regards the prevalence of overweight among school children in the Arab countries, our results are consistent with [9] and [10] in Saudi, [11] in Jordan and [12] in Qatar. On the other hand, our results were much lower than [13] in Kuwait.…”
Section: Discussionsupporting
confidence: 79%
“…The difference in results might be due to the different measurement tools and cut off criteria used. A study conducted among school-aged children found a significantly higher prevalence of obesity among boys and a significantly higher prevalence of overweight among girls (El Mouzan et al, 2010). In addition, a study reported that males showed a higher prevalence of obesity in all age groups studied (Al-Dossary et al, 2010), whereas another study reported higher prevalence of overweight/obesity among girls (Jagadesan et al, 2014).…”
Section: Discussionmentioning
confidence: 90%